PROGRAMAÇÃO DE SISTEMAS DE CONTROLE APLICADOS A ROBÓTICA - Zimmermann, Jeferson; Lima, Pablo V. C. D.; Winik, Saul V.; Reimbold, Manuel M. P.; Martins, Rogerio S. D. M. (Salão do Conhecimento, 2013)
Resumo